Mechanisms Underlying Resistance to FLT3 Inhibitors in Acute Myeloid Leukemia - Motoki Eguchi; Yosuke Minami; Ayumi Kuzume; SungGi Chi (Biomedicines, 2020)
FLT3-ITD and FLT3-TKD mutations were observed in approximately 20 and 10% of acute myeloid leukemia (AML) cases, respectively. FLT3 inhibitors such as midostaurin, gilteritinib and quizartinib show excellent response rates in patients with FLT3-mutated AML, but its duration of response may not be sufficient yet. The majority of cases gain secondary resistance either by on-target and off-target abnormalities. On-target mutations (i.e., FLT3-TKD) such as D835Y keep the TK domain in its active form, abrogating pharmacodynamics of type II FLT3 inhibitors (e.g., midostaurin and quizartinib). Second generation type I inhibitors such as gilteritinib are consistently active against FLT3-TKD as well as FLT3-ITD. However, a “gatekeeper” mutation F691L shows universal resistance to all currently available FLT3 inhibitors. Off-target abnormalities are consisted with a variety of somatic mutations such as NRAS, AXL and PIM1 that bypass or reinforce FLT3 signaling. Off-target mutations can occur just in the primary FLT3-mutated clone or be gained by the evolution of other clones. A small number of cases show primary resistance by an FL-dependent, FGF2-dependent, and stromal CYP3A4-mediated manner. To overcome these mechanisms, the development of novel agents such as covalently-coupling FLT3 inhibitor FF-10101 and the investigation of combination therapy with different class agents are now ongoing. Along with novel agents, gene sequencing may improve clinical approaches by detecting additional targetable mutations and determining individual patterns of clonal evolution.